Les nuits carcérales, révélatrices des violences de l’enfermement - Naomi Fournier (Ateliers d'Anthropologie)
This article shines a light on the life of female prisoners during nocturnal time in a French prison, in order to understand the operation of this punishment and marginalisation phenomenon. This study presents an obvious defamiliarisation and makes it possible to meet, within a concentrated space, people from the widest variety of backgrounds and environments. This text offers a detailed presentation of a first field project in the context of an academic dissertation, which attempts an analysis of incarceration issues relating to its multiple, insidious, permanent brutalities. Night is viewed from within a closed, normed space, to which is added the more subjective and emotional feeling of confinement, showing how night has a destructive effect on the imagination of prisoners.